Osteocutaneous Free Tissue Transplantation for Mandibular Osteoradionecrosis - Chandarana, Shamir P.; Chanowski, Eric J.P.; Casper, Keith A.; Wolf, Gregory T.; Bradford, Carol R.; Worden, Francis P.; Eisbruch, Avraham; Chepeha, Douglas B. (Journal of Reconstructive Microsurgery, 2013)
Objective To describe the success rate, complications, and functional outcomes of patients who are treated with osteocutaneous free tissue transplantation for grade 4 mandibular osteoradionecrosis (ORN).Design Retrospective case series.Setting Tertiary care academic medical center.Patients Twelve patients (8 males, 4 females; mean age, 57.6 years) with grade 4 mandibular ORN. Three patients (25%) had a history of primary radiotherapy, two (17%) had previous concurrent chemoradiation, and seven (58%) had undergone postoperative adjuvant radiotherapy. Ten patients (83%) had previous major ablative surgery to treat the primary tumor and five (50%) had been reconstructed with a free tissue transplant prior to the onset of ORN.Interventions All patients underwent reconstruction with an osteocutaneous free tissue transplant for grade 4 mandibular ORN between 1999 and 2006.Main Outcome Measures Successful treatment of mandibular ORN; major, minor, and late complications; gastrostomy tube (G-tube) dependence; speech and swallowing scores.Results Grade 4 mandibular ORN was successfully treated in eight (73%) evaluable patients. One patient (8%) died of a second primary tumor before the 12-month assessment. Eight patients (67%) had a major complication, three (25%) had a minor complication, and nine (75%) had a late complication. Three of the five G-tube– dependent patients prior to mandibular reconstruction were able to discontinue the use of their G-tube. Seven of the eight successfully treated patients maintained their nutrition by mouth. Median “range of liquids” score was 6/6 (range, 4 to 6). Median “range of solids” score was 4/6 (range, 3 to 6). Median “understandability of speech” score was 4/5 (range, 2 to 5).Conclusions Grade 4 mandibular ORN was treated successfully with an osteocutaneous free tissue transfer in eight evaluable patients (73%). In successfully treated patients, median speech/swallowing scores were highly functional, but the remaining radiated soft tissue resulted in higher local wound complications and a modified diet.
Keywords: osteoradionecrosis; reconstructive surgical procedures; mandible; surgical flaps; head and neck neoplasms